Performativity of Materials in Learning: The Learning-Whole in Action - Lucila Carvalho; Pippa Yeoman (Springer, 2021)
Contemporary educational practices have been calling for pedagogical models that foreground flexibility, agency, ubiquity, and connectedness in learning. These models have, in turn, been stimulating redevelopments of educational infrastructure -with physical contours reconfigured into novel complex learning spaces at universities, schools, museums, and libraries. Understanding the complexity of these innovative learning spaces requires an acknowledgement of the material and digital as interconnected. A 'physical' learning space is likely to involve a range of technologies and in addition to paying attention to these 'technologies' one must understand and account for their physical sites of use as well. This paper discusses the influence of materiality in learning, using an analytical approach that situates learning activity as an emergent process. Drawing on theories that foreground socio-materiality in learning and on the relational perspective offered by networked learning, we call for a deeper understanding of the interplay between the physical (material and digital), conceptual, and social aspects of learning, and their combined influence on emergent activity. The paper argues that in order to successfully design for innovative learning, educators need to develop their capacity to trace the intricate connections between people, ideas, digital and material tools, and tasks -to see the learning-whole in action.